2021
DOI: 10.1108/ijlm-11-2020-0425
|View full text |Cite
|
Sign up to set email alerts
|

Material convergence issue in the pharmaceutical supply chain during a disease outbreak

Abstract: PurposePharmaceutical donations are a practical approach to increase medicine availability during disasters such as disease outbreaks. However, often donated pharmaceuticals are inappropriate and unsuitable. This convergence of inappropriate pharmaceuticals is a severe operational challenge and results in environmental hazards. This study explores the pharmaceutical supply chains (PSCs) during a disease outbreak to relieve the negative impact of the material convergence problem (MCP).Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…We assert that implementing circular economy principles within the pharmaceutical supply chain can substantially improve environmental and operational aspects. opportunity and challenges of reverse logistics and discovered pharmaceuticals to be the most (Patil et al, 2022;Tukamuhabwa et al, 2023). The findings of the present study highlight the link between supply chain management, total quality management and operational performance in the pharmaceutical industry.…”
Section: Solutions For the Pharmaceutical Industrymentioning
confidence: 58%
See 1 more Smart Citation
“…We assert that implementing circular economy principles within the pharmaceutical supply chain can substantially improve environmental and operational aspects. opportunity and challenges of reverse logistics and discovered pharmaceuticals to be the most (Patil et al, 2022;Tukamuhabwa et al, 2023). The findings of the present study highlight the link between supply chain management, total quality management and operational performance in the pharmaceutical industry.…”
Section: Solutions For the Pharmaceutical Industrymentioning
confidence: 58%
“…A study highlights that donors rarely fund the overseas transport cost. Pharmaceutical waste at the disaster site can instigate new cases of infectious disease and pose a threat to the environment (Patil et al, 2022). According to a local Greek pharmacist, individuals frequently do not take their medications as prescribed, which results in waste.…”
Section: Solutions For the Pharmaceutical Industrymentioning
confidence: 99%
“…Nonetheless, even if these technological innovations enhanced PSCs' ability to respond to unexpected risks ensuring more dynamicity, some characteristics of the pharmaceutical sector still deeply affect PSCs' performances and resilience capabilities. That said, even if in recent years PSCs could count on new advanced digital technologies that allow them to achieve a stronger control over the network and flexibility along the chain, evidence from the last great pandemic showed weaknesses in the PSCs that cannot be ignored (Patil et al, 2021). Moreover, to illustrate, as for new technologies integrations, Omar and Basir (2020) reported that disruptions and malpractices still affect PSCs.…”
Section: Current Issues and Challenges Of Global Pscsmentioning
confidence: 99%
“…Sustainability comprises economic, social, and environmental factors that should be considered in a sustainable location and resource allocation model (Clune & Zehnder, 2020; Patil et al, 2021; Purvis et al, 2019). Terouhid et al (2012) suggest six characteristics of a sustainable facility location model.…”
Section: Literature Reviewmentioning
confidence: 99%